Cold-storage of Piezodorus guildinii (Hemiptera: Pentatomidae) eggs for rearing Telenomus podisi (Hymenoptera: Platygastridae) - Cingolani, Maria Fernanda (2015)
Piezodorus guildinii (Hemiptera: Pentatomidae) is an important soybean pest, and one of its main natural enemies is Telenomus podisi (Hymenoptera: Platygastridae). Rearing of the parasitoid is constrained by the hosts' egg quality, which deteriorates after few generations in laboratory, therefore, cold-stored host eggs utilization could be a useful tool for augmentative biological control. Thus, the objective was to evaluate the quality of P. guildinii cold-stored eggs, on the performance of parental and F1 generation of T. podisi. Hosteggs 24 hour old were stored at -18°C for one (N= 53), two (N= 28) or three months (N= 29), and approximately 40 host eggs were offered to a T. podisi female per treatment, for 48 hours. The control treatment consisted of 24-hour-old non-frozen host eggs, obtained and kept at 24°C (N= 55). Parental generation parasitism and progeny´s emergence on frozen eggs was significantly lower than on non-frozen eggs, even for the shorter storage period. Male proportion and preimaginal development time of the progeny increased with freezing period. However, parasitism proportion caused by adults of F1, and emergence, male proportion, and preimaginal development time of F2 were not affected. Although the performance of T. podisi on frozen P. guildinii eggs was significantly lower than on nonfrozen ones, host eggs storage for up to two months allowed obtaining a parasitism rate of 40% with a high emergence rate. This could be helpful enough to maintain mass rearings, mainly during the host hibernation period, and to enhance field parasitism when host is scarce.